PENINGKATAN PEMAHAMAN KONSEP NILAI TEMPAT BILANGAN MELALUI MEDIA KANTONG BILANGAN PADA PESERTA DIDIK KELAS I SDN SUKODONO 1 SIDOARJO - Rihwatus Setya Dewi; Delia Indrawati; Agustin Indah K (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
Looking at the problems found by researchers in grade I of SDN Sukodono 1 Sidoarjo, such as the lack of teachers in the use of learning media in mathematics subjects. Very impactful on the understanding of concepts, learning activities and learning outcomes of students. So that researchers use learning media in the form of number pockets that intend to increase understanding of the concept of place value of a number. The subject of this study were grade I students of SDN Sukodono 1 Sidoarjo with a total of 20 people. Data in this study were collected using observation, test, interview, and documentation techniques. The implementation of class action research (PTK) is carried out in II cycles with each cycle 4 stages, namely: planning, implementation, observation and reflection. The success indicator of PTK is said to be successful if students classically obtain a score greater than or equal to 75. Learning outcomes in the implementation of the first cycle were 45% with an average score of 64,1. And the learning outcomes in the implementation of cycle II are 80% with an average value of 84,75. Based on the result of the research conducted, it can be concluded that using number bag media in learning the place value of a number can increase understanding of concept of number place value. Therefore, it is better if teachers use number pocket learning media as one of the media that can help students in accepting and understanding the concept of place value.